A review on optimistic biorefinery products: Biofuel and bioproducts from algae biomass. (15th April 2023) - Wang, Xuan; Zhang, Yaoli; Xia, Changlei; Alqahtani, Ali; Sharma, Ashutosh; Pugazhendhi, Arivalagan
Graphical abstract: Highlights: Recent biorefinery products from microalgae are discussed in this review. Global demand of bioenergy & microalgae based products are considered in this review. Optimistic methods reported for algae biomass based biofuel discussed. List of bioenergy and bioproducts producing microalgae has been reviewed. Pharmaceutically valuable products are discussed in this review. Abstract: The algae biorefinery ideas have getting lot of attention recently. The newly emerging algae mediated bioeconomy takes precedence to characterizing and tackling significant improvements in biomass, biofuel and bioproducts productivity. Such emerging advancements must be guided by financial and sustainable development fundamentals, which will aid in unravelling the controversial bioproducts-energy-ecosystems interconnection something which algae reside. Acknowledging the metabolic processes of algae's storage energy metabolism to generate bio - fuels as well as bioproducts can shed light on the crucial obstacles which currently limit net carbon utilization and photosynthesis potential, inevitably guiding production efficiency as well as economic potential in the face of limited assets. We reveal numerous possible mechanisms for a theoretical algae biorefinery structure in this analysis, for each item (biofuel and bioproducts) addressing a specific major challenge identified to better future. Researchers connect each promising bioproduct, characterise appropriate conversion and extraction mechanisms, and explain market potential with values related to product commercialization.